Genome-wide identification and expression analysis of the glutathione transferase gene family and its response to abiotic stress in rye (Secale cereale) - Hongli Shi; Ke Wan; Bingde Dou; Yanyan Ren; Lihuan Huo; Chao Zhang; Shuning Yue; Zhongling Li; Huan Guo; Jiakun Dai (BMC Genomics)
Abstract Background Glutathione S-transferases (GSTs) are a crucial class of plant enzymes, playing pivotal roles in plant growth, development, and stress responses. However, studies on the functions and regulatory mechanisms of GSTs in plants remain relatively limited. Results This study aimed to comprehensively identify and analyze GST proteins in rye. A total of 171 rye GST genes were identified and classified into four subfamilies, Tau, Phi, Theta, and Zeta, based on their sequence similarity and structural features. Notably, genes classified under the Tau subfamily were the most abundant at 118, while only one gene was under the Theta subfamily. Subsequent phylogenetic and collinearity analysis revealed 29 tandem duplications and 6 segmental duplication events. There were 13 collinear genes between rye and wheat, maize, and rice, demonstrating the expansion and evolution of the GST gene family. An analysis of the expression profiles of 20 representative ScGST genes in different tissues and under various environmental stresses was performed to further understand the functions and expression patterns of ScGST genes. The results showed that these genes exhibited the highest expression levels in stems, followed by fruits and leaves. Conclusions This study provides a comprehensive identity, classification, and analysis of rye GST genes, which offer valuable insights into the functionality and regulatory mechanisms of the GST gene family in rye. Especially, ScGST39 was identified as a candidate gene because it was significantly upregulated under multiple stress conditions, indicating its potential crucial role in plant stress tolerance mechanisms.